A Study of Inflammatory Markers in Patients with Alcoholic-Fatty Liver Disease and Non-Alcoholic Fatty Liver Disease - Sony, Ashwiani Kumar (International Journal of Psychosocial Rehabilitation, 2024)
Background: Increased levels of various circulating chemicals have been associated with fatty liver disease inflammatory markers.  The difference in the level of increased inflammatory markers between patients with AFLD and NAFLD is still unclear. Aims & Objectives: The aim of the present study was to compare the inflammatory markers between patients with alcoholic-fatty liver disease (AFLD) and non-alcoholic fatty liver disease (NAFLD). mterial and method: This descriptive study included 50 individuals with fatty liver disease (25 NAFLD, 25 AFLD). Venous blood samples were taken from fasting patients to assess inflammatory markers (CRP, IL6, TNF α). Statistical analysis was performed using the student’s t- test, with p-values < 0.05 considered significant. Results: The mean values of inflammatory markers (CRP, IL6, TNF-α a) in the NAFLD group were 1.79±0.11, 27.94±1.22, 35.24±2.6, and in the AFLD group, 1.92±0.16, 29.35±1.38, 36.88±2.19. There were no significant changes in CRP, IL6, or TNF-α levels between AFLD patients and those with NAFLD. Conclusion: Fatty liver disease is associated with increased inflammatory markers. Since increased inflammatory markers in fatty liver disease are indicative of liver injury, due importance should be given to the assessment of inflammatory markers in the management of patients with fatty liver disease.